Legal Principles of Environmental Accounting as Means of Identifying Sustainable Development Indicators in Ukraine - Yermolenko, Volodymyr; Gafurova, Olena; Krasnova, Mariya; Krasnova, Yuliia (European Journal of Sustainable Development, 2020)
The article presents the results of the legal analysis of the formation of environmental accounting as one of the main means of determining the effectiveness of the implemented indicators of sustainable development. It is established that today there are no common approaches around the world to identify sustainable development indicators, including their environmental component. This greatly influences the development of a unified system of environmental accounting, which contains important data on the quantity and quality of natural resources, their legal status, the number of objects and substances that have harmful effects on the environment, financial and other measures taken for the environmental modernization of enterprises , the payment of environmental payments, etc., as such information is a major factor in making further management decisions to achieve sustainability in the environmental field, both locally, nationally, regionally, and globally. tovomu level. Keywords: sustainable development, indicators, ecological accounting, ecological information, reliability of data, types of ecological accounting systems, systematization of ecological accounting systems, regulatory legal regulation of ecological accounting